2005
DOI: 10.1073/pnas.0502450102
|View full text |Cite
|
Sign up to set email alerts
|

A prokaryotic superoxide dismutase paralog lacking two Cu ligands: From largely unstructured in solution to ordered in the crystal

Abstract: Little is known about prokaryotic homologs of Cu,Zn superoxide dismutase (SOD), an enzyme highly conserved among eukaryotic species. In 138 Archaea and Bacteria genomes, 57 of these putative homologs were found, 11 of which lack at least one of the metal ligands. Both the solution and the crystal structures of the SOD-like protein from Bacillus subtilis, lacking two Cu ligands and found to be enzymatically inactive, were determined. In solution, the protein is monomeric. The available nuclear Overhauser effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 40 publications
2
38
0
Order By: Relevance
“…Similar behavior was observed in the SOD-like protein from Bacillus subtilis (27), where its NMR properties indicate a conformational mobility for most of the protein, characterized by defined secondary-structure elements and a dynamic tertiary structure, at variance with the X-ray crystal structure of the same protein, which shows a well-ordered tertiary structure.…”
Section: Resultssupporting
confidence: 63%
“…Similar behavior was observed in the SOD-like protein from Bacillus subtilis (27), where its NMR properties indicate a conformational mobility for most of the protein, characterized by defined secondary-structure elements and a dynamic tertiary structure, at variance with the X-ray crystal structure of the same protein, which shows a well-ordered tertiary structure.…”
Section: Resultssupporting
confidence: 63%
“…The case of Bacillus subtilis superoxide dismutase While facing the difficult task to crystallize a superoxide dismutase-like protein from Bacillus subtilis (BsSOD) we ran some NMR experiments, which revealed that BsSOD was only partially structured in solution 61,107 . The NMR data demonstrated the existence of secondary structure elements that fluctuate over several different conformations in solution.…”
Section: Anticipated Resultsmentioning
confidence: 99%
“…We then set up a screen by using Zn(II) concentration as a variable and eventually we were able to grow well diffracting crystals of the protein. Step Problem Possible reason Solution located at the surface of the protein 61 . The coordination bonds promote a transition from a disordered structure to a completely folded structure of BsSOD.…”
Section: Anticipated Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal ions in proteins are responsible for multiple tasks. They help stabilizing protein structure [4], induce conformational changes [5][6][7], and assist protein functions (e.g. electron transfer, nucleophilic catalysis).…”
Section: Introductionmentioning
confidence: 99%